Prophylactic plasma transfusion for surgical patients with abnormal preoperative coagulation tests: a single-institution propensity-adjusted cohort study. Issue 3 (March 2016) - Jia, Qing; Brown, Michael J; Clifford, Leanne; Wilson, Gregory A; Truty, Mark J; Stubbs, James R; Schroeder, Darrell R; Hanson, Andrew C; Gajic, Ognjen; Kor, Daryl J
Summary: Background: Perioperative haemorrhage negatively affects patient outcomes and results in substantial consumption of health-care resources. Plasma transfusions are often administered to address abnormal preoperative coagulation tests, with the hope to mitigate bleeding complications. We aimed to assess the associations between preoperative plasma transfusion and bleeding complications in patients with elevated international normalised ratio (INR) undergoing non-cardiac surgery. Methods: We did an observational study in a consecutive sample of adult patients undergoing non-cardiac surgery with preoperative INR greater than or equal to 1·5. The exposure of interest was transfusion of preoperative plasma for elevated INR. The primary outcome was WHO grade 3 bleeding in the early perioperative period (from entry into the operating room until 24 h following exit from operating room). Hypotheses were tested with univariate and propensity-matched analyses. We did multiple sensitivity analyses to further evaluate the robustness of study findings. Findings: Between Jan 1, 2008, and Dec 31, 2011, we identified 1234 (8·4%) of 14 743 patients who had an INR of 1·5 or above and were included in this investigation. Of 1234 study participants, 139 (11%) received a preoperative plasma transfusion. WHO grade 3 bleeding occurred in 73 (53%) of 139 patients who received preoperative plasma compared with 350 (32%) of 1095 patients who did not (odds ratio [OR] 2·35, 95% CI 1·65–3·36; p<0·0001). Among the propensity-matched cohort, 65 (52%) of 125 plasma recipients had WHO grade 3 bleeding compared with 97 (40%) of 242 of those who did not receive preoperative plasma (OR 1·75, 95% CI 1·09–2·81; p=0·021). Results from multiple sensitivity analyses were qualitatively similar. Interpretation: Preoperative plasma transfusion for elevated international normalised ratios was associated with an increased frequency of perioperative bleeding complications. Findings were robust in the sensitivity analyses, suggestive that more conservative management of abnormal preoperative international normalised ratios is warranted. Funding: Mayo Clinic, National Institutes of Health.